Food risk trade‐off in the Indo‐Pacific humpback dolphin: An exploratory case study. Issue 4 (23rd January 2020) - Lin, Mingli; Caruso, Francesco; Liu, Mingming; Lek, Sovan; Li, Kuan; Gozlan, Rodolphe E.; Li, Songhai
Abstract: Based on optimal foraging theory, animals are expected to maximize foraging benefits whilst minimizing risks. Despite risking being subjected to anthropogenic impacts such as water contamination, marine traffic, and underwater noise, estuaries have been identified as the preferred habitat of the Indo‐Pacific humpback dolphin ( Sousa chinensis, IPHD). However, it remains unclear why this vulnerable species favours such risky habitats. Here, an exploratory case study in Zhanjiang estuary, China, was conducted to test the hypothesis that IPHDs select estuarine habitats as a trade‐off that maximizes foraging opportunities whilst minimizing the risk of mortality. The results showed that IPHDs accept greater mortality risks for higher food rewards but select habitats with lower risks when food rewards are similar between two locations. Although this type of information is important for underpinning models for individual dolphins, its principal role is to show environmental protection agencies why IPHDs favour estuaries despite the increased mortality risks. Habitat conservation plans should carefully consider prey stocks, possibly through the presence of marine protected areas near estuaries, as local overfishing may lead vulnerable cetacean populations to take greater risks.